2016
DOI: 10.1080/01621424.2016.1227009
|View full text |Cite
|
Sign up to set email alerts
|

A cost analysis of remote monitoring in a heart failure program

Abstract: In this study, we examine the cost per outcomes of remote monitoring services in home health care. The methodology followed case matched design via retrospective chart reviews. Results of the chi-square test suggest that there were no significant associations between the intervention and hospital readmissions, χ = (1, n = 210, p-value = .71, phi = .71). An independent t-test compared group means of the number of skilled nursing visits and agency costs, p-value of .002 and .000, respectively, favoring the stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Patient inclusion criteria for previous hospitalizations differed among the studies. If a hospital admission was required for inclusion, this was most often (n=10) within 7 days of discharge [ 4 , 23 , 24 , 29 , 35 , 37 , 39 - 42 ]. Inclusion was started within 1 month of index hospitalization for 2 studies [ 20 , 25 ], and 5 studies [ 21 , 32 , 43 - 45 ] included patients within 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient inclusion criteria for previous hospitalizations differed among the studies. If a hospital admission was required for inclusion, this was most often (n=10) within 7 days of discharge [ 4 , 23 , 24 , 29 , 35 , 37 , 39 - 42 ]. Inclusion was started within 1 month of index hospitalization for 2 studies [ 20 , 25 ], and 5 studies [ 21 , 32 , 43 - 45 ] included patients within 6 months.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 9 studies reported outcome measures related to non-ED health care visits. These visits comprised outpatient visits [ 20 , 22 , 23 , 26 , 36 , 45 , 47 ], primary care visits [ 33 , 45 ], home visits by nurse [ 37 , 45 ], urgent care visits [ 33 ], and telephone contacts [ 47 ]. Most (6/9, 67%) of these studies found that their telemonitoring intervention was associated with a significant increase in non-ED health care visits [ 22 , 23 , 26 , 33 , 37 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, RPM has been shown to reduce health service utilization and costs (e.g., hospitalization and emergency room (ER) visits) among patients with CHF [2,[8][9][10][11][12], whereas other studies did not find similar findings [6,7,13,14]. Furthermore, some studies reported inconclusive findings [15][16][17].…”
Section: Introductionmentioning
confidence: 57%
“…There has been an increasing amount of literature on the potential value of RPM for patients with COPD and/or CHF; however, literature has shown both supportive and opposing evidence for RPM [1,6,7]. For example, RPM has been shown to reduce health service utilization and costs (e.g., hospitalization and emergency room (ER) visits) among patients with CHF [2,[8][9][10][11][12], whereas other studies did not find similar findings [6,7,13,14].…”
Section: Introductionmentioning
confidence: 83%
“…A growing amount of literature exists on the potential value of RPM for patients with COPD and CHF; however, the literature has shown both supportive and opposing evidence for RPM [1,6,7]. For example, RPM has been shown to reduce health service utilization and costs (eg, hospitalization and emergency room [ER] visits) among patients with CHF [2,8-12], whereas other studies did not find similar findings [6,7,13,14]. Conversely, some studies reported inconclusive findings [15-17].…”
Section: Introductionmentioning
confidence: 99%